2011
DOI: 10.1111/j.1740-8709.2011.00343.x
|View full text |Cite
|
Sign up to set email alerts
|

A household‐level sweet potato‐based infant food to complement vitamin A supplementation initiatives

Abstract: Vitamin A deficiency (VAD) prevalence in Sub-Saharan Africa is high in spite of vitamin A supplementation programmes among children in most countries. Plant-based complementary foods remain the key source of nutrients in addition to breast milk for infants in lower income countries. Cereal-legume blends are superior in protein and energy densities compared with maize, millet or sorghum-only porridge. However, unfortified cereal-legume and cereal-only porridges are low in vitamin A. A household-level sweet pota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
33
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 21 publications
(46 reference statements)
2
33
0
Order By: Relevance
“…Low et al 42 reported that studies conducted in sub-Saharan Africa demonstrated that consumption of boiled orangefleshed sweet potato improved vitamin A status of children. A separate study by Amagloh 43 confirmed that orange-fleshed sweet potato was high in vitamin A and could be used as a complementary food in infant feeding. To improve the consumption of this vitamin A rich type of sweet potato, Laurie and Van Heerden 44 prepared different food types (chips, doughnuts, juice from the roots and a green leafy dish from the leaves) from orange-fleshed sweet potato to determine consumer acceptability.…”
Section: Sweet Potato For Combating Vitamin a Deficienciesmentioning
confidence: 99%
“…Low et al 42 reported that studies conducted in sub-Saharan Africa demonstrated that consumption of boiled orangefleshed sweet potato improved vitamin A status of children. A separate study by Amagloh 43 confirmed that orange-fleshed sweet potato was high in vitamin A and could be used as a complementary food in infant feeding. To improve the consumption of this vitamin A rich type of sweet potato, Laurie and Van Heerden 44 prepared different food types (chips, doughnuts, juice from the roots and a green leafy dish from the leaves) from orange-fleshed sweet potato to determine consumer acceptability.…”
Section: Sweet Potato For Combating Vitamin a Deficienciesmentioning
confidence: 99%
“…However, diluting the paste to reduce the viscosity leads to energy and nutrient thinning (that is, the reduction of energy and nutrient densities). Therefore, a household-level sweetpotato-based complementary food has been suggested as a more suitable complementary food as it would be lower in starch resulting in a less viscous porridge compared with a maize-based infant product (5). …”
mentioning
confidence: 99%
“…Weanimix was developed in 1987 in Ghana through collaboration between UNICEF and the Nutrition Unit of the Ministry of Health, Ghana; it contains maize, groundnut, and soyabean or cowpea (14, 15), and it is an improved complementary food compared with traditional cereal-only porridge in energy and protein (15). In our studies, Weanimix was slightly modified by using dehulled maize and soyabean instead of using non-dehulled ingredients, and denoted as enriched Weanimix (5, 16, 17). The extrusion-cooked ComFa and roller-dried ComFa contained 83% of the protein content of 15 g/100 g recommended by the Codex Alimentarius Commission (1), but the oven-toasted ComFa and enriched Weanimix met the protein specification.…”
mentioning
confidence: 99%
“…Infants and toddlers are at increased risk for ID and VAD when complementary foods, which are usually cereal-based, are introduced [4]. These cereal-based foods are often poor dietary sources of both vitamin A [5,6] and bioavailable iron as they contain high levels of iron absorption inhibitors such as phytates [7,8], or polyphenols [8]. The ideal complementary food should have adequate levels of nutrients and high mineral bioavailability [9].…”
Section: Introductionmentioning
confidence: 99%
“…Sweet potato-based complementary food formulations, prepared from cream- or orange-fleshed sweet potato (CFSP or OFSP, respectively) cultivars, contain significantly more β-carotene, the precursor of vitamin A, than cereal-based products [5,6]; have acceptable sensory attributes [10,11]; and, desirable physical properties, such as viscosity, for complementary feeding [10,11]. Additionally, sweet potato is relatively low in phytate compared to cereals [12,13], thus it would be expected that the sweet potato food matrix would have a less inhibitory effect on iron absorption in human infants.…”
Section: Introductionmentioning
confidence: 99%